Effectiveness of Photogem (R) activated by LED on the decontamination of artificial carious bovine dentin - Giusti, J. S. M.; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Pizzolitto, A. C.; Kurachi, C.; Bagnato, V. S. (Springer, 2006)
The aim of this study was the evaluation of the effectiveness of photodynamic therapy on the decontamination of artificially induced carious bovine dentin, using Photoge(R) as the photosensitizer agent and an LED device as a light source. Dentin samples obtained from bovine incisors were immersed in sterile broth supplemented by Lactobacillus acidophillus 10(8) colony formation units (CFU) and Streptococcus mutans 10 8 CFU. Different concentrations of photosensitizer, PA = 1 mg/ml, PB = 2 mg/ml, and PC = 3 mg/ml, and two fluences, D = 24 J/cm(2) and D = 48 J/cm(2), were investigated. After CFU counting per milligram of carious dentin and statistical analysis, we observed that the photodynamic therapy (PDT) parameters used were effective for bacterial reduction in the in vitro model under study. The best result was achieved with the application of Photoge(R) at 2 mg/ml and photoactivated under 24 J/cm(2) showing a survival factor of 0.14. At higher photosensitizer concentrations, a higher dark toxicity was observed. We propose a simple mathematical expression for the determination of PDT parameters of photosensitizer concentration and light fluence for different survival factor values. Since LED devices are simpler and cheaper compared to laser systems, it would be interesting to verify their efficacy as a light source in photodynamic therapy for the decontamination of carious dentin.